2019
DOI: 10.5465/ambpp.2019.134
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Responses to Bureaucratic Red Tape

Abstract: This study investigates how varying conditions of administrative delay, administrative burden, and rule dysfunctionality spark discrete emotional reactions. Physiological measurements from 136 participants in a laboratory study show that bureaucratic red tape evokes significant negative emotional responses, especially confusion, frustration, and anger, regardless of the favorability of procedural outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Broadly, there is evidence that administrative burdens affect psychological outcomes in different ways 17 . Lab‐based experimental studies have shown negative physiological reactions to compliance burdens, like filling out complicated paperwork 18 . They also may be the more direct result of features embedded in health care processes.…”
Section: What Are Health Care Administrative Burdens?mentioning
confidence: 99%
“…Broadly, there is evidence that administrative burdens affect psychological outcomes in different ways 17 . Lab‐based experimental studies have shown negative physiological reactions to compliance burdens, like filling out complicated paperwork 18 . They also may be the more direct result of features embedded in health care processes.…”
Section: What Are Health Care Administrative Burdens?mentioning
confidence: 99%